Prerequisites for effective isolated limb perfusion using tumour necrosis factor alpha and melphalan in rats - Wilt, J H W de (Nature Publishing Group, 1999)
An isolated limb perfusion (ILP) model using soft tissue sarcoma-bearing rats was used to study prerequisites for an effective ILP, such as oxygenation of the perfusate, temperature of the limb, duration of the perfusion and concentration of tumour necrosis factor (TNF). Combination of 50 μg TNF and 40 μg melphalan demonstrated synergistic activity leading to a partial and complete response rate of 71%. In comparison to oxygenated ILP, hypoxia was shown to enhance anti-tumour activity of melphalan alone and TNF alone but not of their combined use. Shorter perfusion times decreased anti-tumour responses. At a temperature of 24–26°C, anti-tumour effects were lost, whereas temperatures of 38–39°C or 42–43°C resulted in higher response rates. However, at 42–43°C, local toxicity impaired limb function dramatically. Synergy between TNF and melphalan was lost at a dose of TNF below 10 μg in 5 ml perfusate. We conclude that the combination of TNF and melphalan has strong synergistic anti-tumour effects in our model, just as in the clinical setting. Hypoxia enhanced activity of melphalan and TNF alone but not the efficacy of their combined use. For an optimal ILP, minimal perfusion time of 30 min and minimal temperature of 38°C was mandatory. Moreover, the dose of TNF could be lowered to 10 μg per 5 ml perfusate, which might allow the use of TNF in less leakage-free or less inert perfusion settings. © 1999 Cancer Research Campaign